In vitro quality assurance of three-dimensional conformal radiotherapy mono-isocentric plan for simultaneous treatment of two targets - Baba, Misba Hamid; Singh, Benoy Kumar (International Journal of Health Sciences, 2021)
Objective: The purpose of this study was to check the in vitro efficacy of a radiotherapy plan generated for the treatment of two femoral targets simultaneously in the pelvis. Methods: The target positions for conformal radiotherapy were simulated by joining two identical water phantoms (approximating the patient dimensions), and a treatment plan to treat the two targets simultaneously with a common isocenter was planned. Calculations were made with a dose prescription of 300cGy to each lesion. The plan was executed on a medical linear accelerator and verified for point doses for individual targets with two ion chambers. Two-dimensional dose verification for fluence was also performed using an array detector of ion chambers (I’mRTMatriXX) to further validate the technique. Results: The minimum, mean and maximum dose in centiGray(cGy) covered by both Ionization Chamber-1 (IC-1) and Ionization Chamber-2 (IC-2) was 295, 303 and 307 as per dose statistics from the treatment plan. The global dose max obtained from the plan was 307 cGy. Measured point doses to both the targets were within ±2%. Dose Difference and Distance to agreement (3%, 3 mm criteria) criteria also passed for 2Dfluence verification. Conclusions: Radiotherapy of two or multiple targets using monoisocentric technique can appreciably reduce the scatter dose to the normal surrounding tissue around the target/s and also the required setup and treatment time is reduced significantly. Therefore, the technique can be efficiently used to save time without compromising the radio therapeutic ratio and quality treatment, for both palliative and curative intent.